The mistletoe favor - Kemerer, Jill (Kemerer, Jill. Wyoming ranchers, 2022)
"After gaining guardianship of his half sister, wealthy rancher Mac Tolbert hopes a part-time job during the holidays will help the grieving teenager. New coffee shop owner Bridget Renna has been on her own since sixteen and is immediately drawn to the shy orphan--and her handsome brother. But as Bridget grows closer to the siblings, will her troubled past ruin their chance at a Christmas together?"--